2018
DOI: 10.1177/0954008318801911
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of a novel high-temperature vinylpyridine-based phthalonitrile polymer

Abstract: A novel vinylpyridine-based phthalonitrile monomer, 2,6-bis[3-(3,4-dicyanophenoxy)styryl]pyridine (BDSP), was resoundingly produced by a nucleophilic substitution reaction of 2,6-bis(3-hydroxystyryl)pyridine with 4-nitrophthalonitrile in the presence of potassium carbonate. The chemical structure of the synthesized BDSP was confirmed by proton (1H) and carbon (12C) nuclear magnetic resonance (NMR) as well as Fourier transform infrared (FTIR) analysis. The curing behavior of BDSP was investigated by FTIR and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…It is worth noting that although the molecular structure of BCPD and BCPM monomer is similar, the T m of BCPD monomer is much lower than that of the BCPM monomer in our previous study. An analogous phenomenon also appears in other reported monomers [ 11 , 22 ]. However, one of the differences between BCPD and BCPM monomer is that the former is non-crystalline, while the latter is crystalline.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It is worth noting that although the molecular structure of BCPD and BCPM monomer is similar, the T m of BCPD monomer is much lower than that of the BCPM monomer in our previous study. An analogous phenomenon also appears in other reported monomers [ 11 , 22 ]. However, one of the differences between BCPD and BCPM monomer is that the former is non-crystalline, while the latter is crystalline.…”
Section: Resultssupporting
confidence: 88%
“…It is suggested that monomers with low T m are usually amorphous [ 11 , 23 , 25 ], while monomers with high T m are usually crystalline [ 4 , 20 , 22 , 23 ]. In previous studies, increasing the flexibility of molecular segments is the main strategy for reducing the T m .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, researchers basically believe that CN polymerization mainly produces triazine, isoindole and phthalocyanine rings, [31][32][33][34][35][36][37][38][39][40][41][42] does not produce small molecules, and gives the polymerization mechanism of forming the three heterocycles. However, this does not explain the experimental results in this paper very well.…”
Section: The Possible Polymerization Mechanism Of 4-apnmentioning
confidence: 99%
“…The bulk addition polymerization of aromatic compounds at high temperatures using compounds containing amino or hydroxyl groups as curing agent is usually the method to prepare phthalonitrile resin. Common curing agents are 4,4′‐diaminodiphenyl (ODA), bis[4(4‐aminophenoxy)phenyl] sulfone (p‐BAPS), APPH and other complex curing agents …”
Section: Introductionmentioning
confidence: 99%